2006
DOI: 10.1103/physrevlett.96.246802
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Poissonian Shot Noise in Graphene

Abstract: We calculate the mode-dependent transmission probability of massless Dirac fermions through an ideal strip of graphene (length L, width W, no impurities or defects) to obtain the conductance and shot noise as a function of Fermi energy. We find that the minimum conductivity of order e 2 =h at the Dirac point (when the electron and hole excitations are degenerate) is associated with a maximum of the Fano factor (the ratio of noise power and mean current). For short and wide graphene strips the Fano factor at th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

92
1,050
5
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 869 publications
(1,150 citation statements)
references
References 17 publications
(23 reference statements)
92
1,050
5
1
Order By: Relevance
“…novel electronic properties such as negative index of refraction 6 , specular Andreev reflections at graphene-superconductor junctions 7,8 , evanescent transport 9 , anomalous phonon softening 10 , etc. A basic assumption behind these intriguing predictions is that the graphene layer is minimally affected by interactions with the environment.…”
mentioning
confidence: 99%
“…novel electronic properties such as negative index of refraction 6 , specular Andreev reflections at graphene-superconductor junctions 7,8 , evanescent transport 9 , anomalous phonon softening 10 , etc. A basic assumption behind these intriguing predictions is that the graphene layer is minimally affected by interactions with the environment.…”
mentioning
confidence: 99%
“…
Graphene, a one-atom thick zero gap semiconductor [1,2], has been attracting an increasing interest due to its remarkable physical properties ranging from an electron spectrum resembling relativistic dynamics [3,4,5,6,7,8,9,10,11,12] to ballistic transport under ambient conditions [1,2,3,4]. The latter makes graphene a promising material for future electronics and the recently demonstrated possibility of chemical doping without significant change in mobility has improved graphene's prospects further [13].
…”
mentioning
confidence: 99%
“…Using a cryogenic, lownoise amplification set-up, we measure shot noise as a function of the gate voltage in two-terminal field-effect graphene devices. The results are successfully compared with the theoretical values derived by solving the Dirac equation [2,3]. Even though the shot noise at the Dirac point is equivalent to that of a regular diffusive conductor, clear distinction in the noise behavior can be found in the gate dependence.…”
Section: Introductionmentioning
confidence: 49%
“…It has been theoretically shown that in perfect graphene at the Dirac point, the conduction occurs only via evanescent waves, i.e. via tunneling between the leads [2,3]. This has interesting consequences on the conductivity and on the shot noise, both of which display universal behavior in the limit of wideaspect-ratio sheets.…”
Section: Introductionmentioning
confidence: 99%